Pengaruh Model Project Based Learning Terintegrasi Musik Tong-Tong terhadap Kemampuan Berpikir Kritis Siswa Kelas V SDIT Ulil Albab Kamal Bangkalan - Syailil Aliyah; Bagus Rahmad Wijaya (Mataram University, 2026)
The challenges of 21st-century education require students to possess strong critical thinking skills; however, science learning in schools is often still theoretical and detached from the students' local cultural context. This study aimed to analyze the influence of the Tong-tong music-integrated Project-Based Learning (PjBL) model on the critical thinking skills of fifth-grade students regarding sound wave material. The research method employed was a quasi-experimental approach with a non-equivalent control group design. Data were collected using validated critical thinking skill test instruments. The results of hypothesis testing using the Independent Sample T-Test showed a significance value of 0.011 (< 0.05), indicating that there was a significant effect of the implementation of the Project Based Learning model integrated with tong-tong music on students’ critical thinking skills. The integration of tong-tong music as a form of local culture in learning helped create a more contextual learning experience and actively engaged students in the learning process.